PENGARUH KOMPETENSI, LOYALITAS, DAN KOLABORATIF TERHADAP KINERJA KARYAWAN PT PLN (PERSERO) UNIT PELAKSANA TRANSMISI PALEMBANG - firmansyah, Medi; Yustini, Tien (LPPM STIE Muhammadiah Bandung, 2023)
This study aims to analyze the effect of competence, loyalty, and collaboration on the performance of employees of PT. PLN (Persero) Palembang transmission implementing unit. The method used in this research is descriptive quantitative method using multiple linear regression analysis. The research data is in the form of questionnaires with all employees of PT. PLN (Persero) Palembang Transmission implementing unit as many as 183 employees. The analysis technique uses classical assumptions, instrument tests, linear regression, and hypotheses with the SPSS version 25 for windows program. Based on the results of partial research (t test) shows that the competency variable has a significant effect on employee performance, the loyalty variable has a significant effect on employee performance and the collaborative variable has a significant effect on employee performance. The results of the simultaneous study (f test) showed a significant value of 0.000 less than 0.05 meaning that Ho was rejected and Ha was accepted, so it was concluded that competency, loyalty and collaborative influence significantly affect the performance of employees of PT PLN (Persero) Palembang transmission implementing unit.